Evaluation of the physical and mechanical properties of concrete blocks with the incorporation of sawdust, polystyrene beads and rubber (Gaceta Técnica, 2025)
In this research, it was decided to incorporate reusable materials, such as sawdust, polystyrene beads, and rubber, in the manufacture of concrete blocks, with the purpose of evaluating their physical and mechanical properties. A total of 315 samples were manufactured using a block-making machine, with molds measuring 12 cm x 40 cm x 18 cm, with dosages of 1:6, 1:7, and 1:8, and addition percentages of sawdust, polystyrene beads, and rubber of 10% and 20% with respect to the aggregate. Dimensional variation, warping, absorption, and axial compressive strength tests were performed on the concrete blocks, from which it was determined that dimensional variation and warping do not depend exclusively on the addition of polystyrene beads, rubber, and sawdust. Furthermore, it was identified that the blocks with the highest absorption were those corresponding to the incorporation of 20% sawdust with a dosage of 1:8. In terms of axial compressive strength, the optimal percentage of polystyrene and rubber beads added to blocks with 1:6, 1:7, and 1:8 ratios were determined to be 10%, achieving the minimum required stress of 4.90 MPa after 28 days of curing. However, sawdust concrete blocks achieved this strength with a 10% addition and a 1:6 ratio. The results determined the optimal conditions for manufacturing concrete blocks with additional materials, complying with Peruvian Technical Standards and the requirements of the National Building Regulations
Keywords: construction materials; reusable materials; concrete blocks; material strength